Electrocatalytic Activation of Donor–Acceptor Cyclopropanes and Cyclobutanes: An Alternative C(sp3)−C(sp3) Cleavage Mode. (16th June 2021) - Kolb, Simon; Petzold, Martin; Brandt, Felix; Jones, Peter G.; Jacob, Christoph R.; Werz, Daniel B.
Abstract: We describe the first electrochemical activation of D–A cyclopropanes and D–A cyclobutanes leading after C(sp 3 )−C(sp 3 ) cleavage to the formation of highly reactive radical cations. This concept is utilized to formally insert molecular oxygen after direct or DDQ‐assisted anodic oxidation of the strained carbocycles, delivering β‐ and γ‐hydroxy ketones and 1, 2‐dioxanes electrocatalytically. Furthermore, insights into the mechanism of the oxidative process, obtained experimentally and by additional quantum‐chemical calculations are presented. The synthetic potential of the reaction products is demonstrated by diverse derivatizations. Abstract : The first electrochemical activation of donor–acceptor (D–A) cyclopropanes and D–A cyclobutanes has been applied for the formal insertion of molecular oxygen into these compounds. C(sp 3 )−C(sp 3 ) cleavage of the ring moieties was achieved either by direct anodic electrolysis or by utilizing a DDQ‐assisted electrochemical strategy. Quantum‐chemical calculations and supportive experiments provided mechanistic understanding of the electrocatalytic process.